The effect of canal cleansing protocols on cementation of a fiber post to saliva-contaminated root canals. Issue 1 (2nd January 2017) - Yaman, Batu Can; Irmak, Özgür; Orhan, Ekim Onur; Karabucak, Bekir; Ozer, Fusun; Blatz, Markus B.
Abstract: Objective: This study investigated the effect of saliva contamination and cleansing effect of a self-etching primer (SEP), phosphoric acid (PA), chlorhexidine (CHX), and ethanol (EtOH) on the microtensile bond strength (μTBS) of a fiber post cemented with a self-adhesive resin cement (SAC) to root canal dentin. Material and methods: Sixty human lower premolar roots were randomly divided into 10 groups: (1) no saliva contamination, no cleansing (Control); (2) no saliva contamination, cleansing with SEP (NC-SEP); (3) no saliva contamination, cleansing with PA (NC-PA); (4) no saliva contamination, cleansing with CHX (NC-CHX); (5) no saliva contamination, cleansing with EtOH (NC-EtOH); (6) with saliva contamination, no cleansing (SC-NC); (7) with saliva contamination, cleansing with SEP (SC-SEP); (8) with saliva contamination, cleansing with PA (SC-PA); (9) with saliva contamination, cleansing with CHX (SC-CHX); (10) with saliva contamination, cleansing with EtOH (SC-EtOH). After cementation of posts, the roots were transversally sectioned to obtain six slices ( n = 36) followed by μTBS test. Data were analyzed with ANOVA and Tukey HSD tests ( p = 0.05). Results: Saliva contamination and cleansing methods had a significant effect on μTBS values ( p < 0.0001). All cleansing agents improved bond strengths when compared with Control and SC-NC. Cleansing with CHX and ethanol showed lower μTBS values than phosphoric acid and SEP, regardless of saliva contamination ( p < 0.05). Conclusions: Saliva contamination negatively affected bonding performance of SAC to root dentin. However; SEP, PA, CHX and EtOH can be used on contaminated dentin surfaces to optimize bonding performance of self-adhesive cements.